2015
DOI: 10.1007/s10943-015-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping and Substance Use: The Moderating Role of Sex

Abstract: The objectives of this study were to ascertain whether positive and negative religious coping are associated with substance use and to determine whether sex moderates this association. This study utilized a cross-sectional design and examined 349 undergraduate students (103 males and 246 females) at a midsize southeastern university. Participants completed a demographic questionnaire, the Brief RCOPE, and the Drinking and Drug Habits Questionnaire. Results revealed a positive association between negative relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…1,5 Religion has proven to be a protective factor against the use of tobacco and drugs by helping teenagers belonging to religious communities to internalize messages that discourage their use as shown by empirical research. 7,8,9,10,11 However, theoretical gaps and contradictory findings about whether belonging to a religious community has a deterrent effect on substance use has also been highlighted. 5 Although not mainstream, significant research exists that has reported a weak or null influence of religion on drug use.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Religion has proven to be a protective factor against the use of tobacco and drugs by helping teenagers belonging to religious communities to internalize messages that discourage their use as shown by empirical research. 7,8,9,10,11 However, theoretical gaps and contradictory findings about whether belonging to a religious community has a deterrent effect on substance use has also been highlighted. 5 Although not mainstream, significant research exists that has reported a weak or null influence of religion on drug use.…”
Section: Introductionmentioning
confidence: 99%
“…However, key questions remain about positive and negative religious coping. In particular, although studies that have assessed both positive and negative religious coping generally show that associations of negative religious coping are stronger and more consistent than are those of positive religious coping (e.g., Pargament et al, 2000; Pargament, Koenig, Tarakeshwar, & Hahn, 2001; see Ano & Vasconcelles, 2005), studies often examine the associations of positive and negative religious coping with well-being separately (e.g., Amadi et al, 2016; Parenteau, 2016; Tarakeshwar et al, 2006) rather than conjointly. Thus, it is not well established whether positive religious coping may be independently associated with well-being when also taking negative religious coping into account.…”
Section: Introductionmentioning
confidence: 99%
“…A potential confound for this relationship is relation: Individuals with higher levels of religiosity are more likely to live in deprived neighborhoods (Hoverd et al, 2013) and more likely to abstain from substance use (Chitwood et al, 2008;Strawbridge et al, 2001). Further, this association between religiosity and abstinence tends to be stronger for women than for men (Parenteau, 2017;Strawbridge et al, 2001). Additional multilevel studies are needed to explicate the relationships among neighborhood-level SES and individual level sex, religiosity, and substance use.…”
Section: Discussionmentioning
confidence: 99%